2018
DOI: 10.3390/en11071642
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Operation of an Aerothermal Heat Pump in a Residential Building Using Building Information Modelling

Abstract: Heating, cooling and domestic hot water (DHW) are responsible for the largest share of energy use in residential buildings in Spain and play an important role in the implementation of nearly zero-energy buildings (NZEB). Building Information Modelling (BIM) is expected to promote more efficient buildings through evaluation of different design options. BIM can be used as a platform from which to gather information that can be conveyed to energy efficiency simulation tools. The objective of this paper was to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Once the process of being adopted by the Spanish Public Administrations as a tool for energy efficiency certification of buildings has been overcome, it is necessary to continue working on the improvement of the interface and the HVAC system models that integrate EnergyPlus [26]. Last but not least is the need for training to architects and engineers in university graduate and postgraduate courses.…”
Section: Discussionmentioning
confidence: 99%
“…Once the process of being adopted by the Spanish Public Administrations as a tool for energy efficiency certification of buildings has been overcome, it is necessary to continue working on the improvement of the interface and the HVAC system models that integrate EnergyPlus [26]. Last but not least is the need for training to architects and engineers in university graduate and postgraduate courses.…”
Section: Discussionmentioning
confidence: 99%
“…The warm air arriving at the top of the building, instead of being let to the ambient, will be collected and circulated through the evaporator of an air to water heat pump, which will produce hot air and water for the building. Due to the warm temperature at the evaporator, the efficiency of the heat pump will increase with respect to a conventional setting in which the evaporator operates with ambient air [10]. In a first setting, the condenser will heat water stored in a tank, but a second alternative with a latent heat thermal storage system (LHTSS) is considered [11].…”
Section: Introductionmentioning
confidence: 99%
“…In a first setting, the condenser will heat water stored in a tank, but a second alternative with a latent heat thermal storage system (LHTSS) is considered [11]. The operating temperatures at this side will fall in the 55-60 • C range [12], usual for domestic HPWH [10]. The system has been designed for a R410A-based HPWH, although it would be interesting to study a transcritical CO 2 -based HPWH (TC-HPWH) alternative.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, research on carbon emissions reduction has focused on exercising control over emissions from residential buildings during the operation period [8]. At the spatial-temporal scale, carbon emissions from residential buildings during the operation period stem from activities such as heating, cooking, and cooling [9,10]. Carbon emissions from different types of activities have noticeable differences given the geographic heterogeneity of climate and development.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were found by different studies. Cooking, heating, cooling, and illumination were all considered major contributors to carbon emissions [6,10,33,34]. Asaee et al [7] revealed that the obstacles to zero carbon emissions were low energy efficiency and high consumption of fossil fuels.…”
Section: Introductionmentioning
confidence: 99%